INFLUENCER SOSIAL MEDIA SEBAGAI KOMUNIKASI STRATEGIS KEHUMASAN PEMERINTAH PADA ERA DIGITAL - Avi Rudianita Widya (Jurnal Ranah Komunikasi, 2021)
In carrying out government public relations functions and duties as an informer of all forms of activities and building a positive reputation and image of the government, a communication strategy is needed to establish communication with the public which is now increasingly diverse and increasingly complex. The development of information technology and social media which is quite large in Indonesia offers a new form of strategy in the practice of government public relations in Indonesia, one of which is the use of social media influencers. The adaptation of marketing strategies into public relation practices is a new chapter towards Indonesian Public Relations 4.0. The approach to the discussion of this article is using a literature review of previous studies with the topic of social media influencers (SMI) with the aim of providing an overview of the use of social media influencers (SMI) as strategic communication in government public relations in terms of communication elements: message sender, message recipient, message, medium and effects. Through this framework, the results obtained are that in utilizing social media influencers (SMI) as a form of strategic communication in government public relations, public relations practitioners must do 1) planning, by understanding what resources social media influencers have and adjusting them to the goals of the organization, 2) organizing, by always coordinating in the process of creating and distributing messages in order to balancing control and creativity, 3) evaluation by measuring the level of effectiveness of social media influencers as input and future improvements.